Genome-wide ribosome profiling reveals complex translational regulation in response to oxidative stress - Gerashchenko, Maxim V; Lobanov, Alexei V; Gladyshev, Vadim N (Proceedings of the National Academy of Sciences - PNAS, 2012)
Information on unique and coordinated regulation of transcription and translation in response to stress is central to the understanding of cellular homeostasis. Here we used ribosome profiling coupled with next-generation sequencing to examine the interplay between transcription and translation under conditions of hydrogen peroxide treatment in Saccharomyces cerevisiae. Hydrogen peroxide treatment led to a massive and rapid increase in ribosome occupancy of short upstream ORFs, including those with non-AUG translational starts, and of the N-terminal regions of ORFs that preceded the transcriptional response. In addition, this treatment induced the synthesis of N-terminally extended proteins and elevated stop codon read-through and frameshift events. It also increased ribosome occupancy at the beginning of ORFs and potentially the duration of the elongation step. We identified proteins whose synthesis was regulated rapidly by hydrogen peroxide posttranscriptionally; however, for the majority of genes increased protein synthesis followed transcriptional regulation. These data define the landscape of genome-wide regulation of translation in response to hydrogen peroxide and suggest that potentiation (coregulation of the transcript level and translation) is a feature of oxidative stress.